Innovation of European Vocational Education and Training : learning in inter-organisational partnerships and networks - Heikkilä, Eila [Verfasser] (LAP Lambert Academic Publishing, 2010)
"This book studies innovation of European Vocational Education and Training (VET) with focus on social learning and innovation in inter-organisational partnerships and networks. The study builds on theories of social innovation and learning and argues that innovation in partnerships and networks of VET is related to shared learning experiences and competence building to reshape and renew policies and practices of VET in Europe. The study draws upon case studies from three European countries - England, Finland and Germany - to explore social innovation in partnerships and networks between organisations involved in VET in local, regional, national and European contexts." (Verlag, BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; T 1.5 International vergleichende Berufsbildungsforschung; S 2.4 Kooperation; I 2.2 Europa; Berufsbildung; Internationale Zusammenarbeit; Innovation; Soziales Lernen; Netzwerk; Europa; England; Finnland; Bundesrepublik Deutschland